Subtitling Strategies from Javanese to English in Netflix’s Series Gadis Kretek - Reza Anggriyashati Adara; Tiara Melani Suci; Henry Loupias; Mellati Mandasari (Leksema: Jurnal Bahasa dan Sastra, 2026)
Translating subtitles from Javanese into English poses both linguistic and cultural challenges, particularly in conveying culturally specific terms accurately while maintaining readability. This study analyzes the subtitling strategies employed in the Netflix series Gadis Kretek, using Gottlieb’s (1992) framework. A qualitative content analysis was conducted on 104 subtitle instances. The findings reveal that transfer is the most frequently used strategy (46 occurences), indicating that the translator often opted for direct, faithful renderings of the source text without major structural or lexical modifications. Paraphrase (21) and expansion (17) follow, reflecting efforts to restructure sentences for naturalness, clarify implicit meanings, and provide additional context for cultural concepts that lack direct equivalents in English. Less frequently applied strategies include decimation (8), condensation (6), and deletion (5), primarily used to reduce or omit elements due to temporal and spatial constraints inherent in subtitling. Imitation appears only once, reserved for proper names or culturally bound expressions that could be transferred without modification. Overall, the predominance of transfer, paraphrase, and expansion highlights a translator preference for preserving meaning while enhancing accessibility and comprehension for a global audience. The systematic categorization of each instance, including linguistic form, contextual meaning, and cultural relevance, demonstrates that subtitling strategies in Gadis Kretek are applied flexibly and contextually, balancing fidelity to the source language with the practical limitations and cultural expectations of the target audience. These findings offer insights for translators and audiovisual translation researchers in managing culturally specific contents in subtitling.